Answer:
Step-by-step explanation:
Solution - Linear equations with two unknowns y=x−8;y=−2x+1y,x=-5,3See StepsStep by Step SolutionSystem of Linear Equations entered : [1] y - x = -8
[2] y + 2x = 1
Graphic Representation of the Equations : x + y = -8 2x + y = 1
Solve by Substitution :// Solve equation [2] for the variable y [2] y = -2x + 1
// Plug this in for variable y in equation [1] [1] (-2x+1) - x = -8
[1] - 3x = -9
// Solve equation [1] for the variable x [1] 3x = 9
[1] x = 3
// By now we know this much : y = -2x+1
x = 3// Use the x value to solve for y y = -2(3)+1 = -5
Solution : {y,x} = {-5,3}